Screening for Chagas Disease Should Be Included in Entry-to-Care Testing for At-Risk People With Human Immunodeficiency Virus (HIV) Living in the United States . (18th February 2022) - Clark, Eva H; Marquez, Carina; Whitman, Jeffrey D; Bern, Caryn
Abstract: Chagas disease screening of at-risk populations is essential to identify infected individuals and facilitate timely treatment before end-organ damage occurs. Coinfected people with human immunodeficiency virus (PWH) are at risk for dangerous sequelae, specifically Trypanosoma cruzi reactivation disease. Recently published national recommendations indicate that at-risk PWH, particularly those from endemic areas or born to women from endemic areas, should be screened via a sensitive anti- T. cruzi IgG assay. However, immunocompromised patients with negative serologic results may warrant further investigation. Reactivation should be suspected in at-risk, untreated PWH with low CD4 cell counts presenting with acute neurologic or cardiac symptoms; these patients should be promptly evaluated and treated. One pragmatic solution to improve Chagas disease screening among PWH and thereby reduce T. cruzi –related morbidity and mortality is to incorporate Chagas disease screening into the panel of tests routinely performed during the entry-to-care evaluation for at-risk PWH. Abstract : Chagas disease can have dangerous sequelae in coinfected people with HIV (PWH). Here we offer practical recommendations to improve diagnosis and care of coinfected PWH, including incorporating Chagas disease screening into the entry-to-care evaluation at HIV diagnosis.